Modified Taylor Complex Figure: Normative data from 290 adults. Issue 2 (6th May 2013) - Casarotti, Alessandra; Papagno, Costanza; Zarino, Barbara
<x xml:space="preserve">Abstract</x> Data for copying and delayed recall (after a 15‐min delay) of the Modified Taylor Complex Figure (MTCF), an alternative form of the Rey‐Osterrieth Complex Figure (ROCF), were collected from 290 healthy participants. Normative data are provided. Age and education were significantly correlated with MTCF scores and must be corrected for to interpret results accurately. More specifically, increasing age adversely affected performance, whereas a higher education resulted in a better performance. Twenty‐five participants were tested with both complex figures (MTCF and ROCF) in two separate sessions to assess correlation, which proved to be high. The collected data allow using the MTCF as a valid alternative material for testing visual long‐term memory avoiding implicit learning that can occur when the same version of the ROCF is used for repeated testing sessions.